Evaluación de riesgos mayores en el Gobierno Autónomo Descentralizado Parroquial de Pumallacta en el año 2024. - Ortega Paucar, Jaime Fernando (2025)
Risk combines the likelihood of a hazardous event and the severity of the resulting damage. This research project aimed to assess major risks in the Decentralized Autonomous Government (GAD) of the Pumallacta Parish in 2024 to minimize the impact on the facility and ensure the safety of individuals. Pumallacta's geographic location exacerbates its vulnerability to natural threats such as earthquakes, volcanic eruptions, fires, and landslides. Surveys were conducted among beneficiaries to evaluate and identify risks. The first method was the matrix of hazards and vulnerabilities, resulting in the following risks: seismic, landslides, fires, and epidemics. Methods such as the MEIPEE were applied; this approach made it possible to quantify the risk associated with hazards, identifying a MEDIUM risk from earthquakes and floods and a HIGH risk from volcanic eruptions and ash fall. The structural vulnerability index for earthquakes was evaluated using the FEMA 154 method, resulting in a LOW level of vulnerability. The NFPA method was used to analyze fire-related risks, showing that the upper floor has the highest combustible load, classifying the risk as HIGH, while the lower floor has a LOW level of risk. As part of the subsequent actions, mitigation measures were designed, such as first aid training led by local medical personnel and firefighting training provided by the Alausí Fire Department. Finally, based on the risk assessment results, an emergency plan was developed for the Pumallacta Parish GAD. This plan and the training activities enhanced the organization's response capacity in the face of emergencies.